Intercultural perspectives of Gregory Bateson's way of thinking - Lavinia Bianchi (Firenze University Press, 2020)
This article proposes a reading of some constructs extrapolated from the boundless work of Gregory Bateson in an educational and markedly intercultural key. In the light of the "new" educational needs of the children of a multicultural, liquid and interconnected society, a renewed ecological education aimed at citizenship is desirable. global. Bateson's teaching can represent an opportunity for reflection for those responsible for educational planning.